Preliminary study on a novel minimally invasive extra-articular implant for unicompartmental knee osteoarthritis. (May 2019) - Saeidi, Mehdi; Ramezani, Maziar; Kelly, Piaras; Neitzert, Thomas; Kumar, Pranesh
Highlights: A new extra-articular implant has been developed for osteoarthritic knees. A patient specific 3D model of the implant was designed on an anatomically accurate knee model. The applied implant can be used without sacrificing any ligaments or modifying the bones. Accurate material properties for hard and soft tissues in the finite element knee model were considered. The new implant partially unloaded the knee joint in the full extension knee position. Abstract: The purpose of this research was to study the efficacy of a novel implant for osteoarthritic knees. This implant is designed to eliminate excessive loads through the knee and to provide suitable conditions for possible tibiofemoral cartilage repair. The implant was designed for the medial side of the knee joint. Finite Element Analysis (FEA) was performed for an extended knee position of the knee joint. Von Mises stress and contact pressure distributions on the medial and lateral compartments were investigated as well as stress distributions throughout the implant's plates. Comparison of FEA results with and without the implant showed that the maximum von Mises stress and contact pressure experienced by the femoral cartilage were reduced by 40% and 35%, respectively, after introducing the implant. Furthermore, after attaching the implant, the femur was slightly abducted and more stress and pressure were perceived in the lateral compartment compared to the model without implant. The maximum von Mises stress in the implant (96 MPa) was far lower than the yield strength of Ti–6Al–4V (∼900 MPa), the selected material for manufacturing the implant. According to the above points, this initial study shows promise for the new prosthesis.